PENGARUH MOTIVASI BERPRESTASI, MINAT, DAN SIKAP TERHADAP HASIL BELAJAR MATEMATIKA KELAS V SEKOLAH DASAR - Rusianingsih, Cucu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe achievement of learning performance should appropriate with the efforts of students. Learning performance of class 5th students at Elementary School 16 City Pontianak on Mathematic is not optimal because it is still 60% under the rate of class grade. Therefore, the research about factors that affected the learning result such as achievement motivation, interest and attitude for students in mathematic learning is need to be made. This research is aimed to know the effect of achievement motivation, interest and attitude toward the mathematic learning performance for Class 5th students of Elementary School 16 City Pontianak. This research used descriptive method with quantitative approach and is also population research with the population of research is 27 students. The instrument of this research is questionnaire and question test and the data analysis technique that used is descriptive statistic technique. The examination of hypothesis used the regression analysis formulation. The result of the research shows that achievement motivation, interest and attitude is giving good effect toward the mathematic learning performance of class V students of Elementary School 16 City Pontianak.Key words: achievement motivation, interest, attitude, mathematic learning performance.